Primary cutaneous apocrine carcinoma of the scalp: A rare case report - Balasubramanian, Rohit; Ali, Sheena; Manohar, A; Mehta, Sangita (Asian Journal of Neurosurgery, 2021)
Primary cutaneous apocrine carcinoma of the scalp is a rare adnexal sweat gland neoplasm. It is most commonly observed over eyelids and ear canals and is often confused with dermoid and epidermoid cysts, lipomas, cutaneous metastatic lesions, or basal cell carcinomas. We describe a 66-year-old male who presented with a midline scalp lesion. He was treated surgically with a wide local excision.
Keywords: Neck node dissection; palliative radiotherapy; primary cutaneous apocrine carcinoma; wide local excision